Optical Evaluation on Delamination Buckling of Composite Laminate with Impact Damage - J. T. Ruan; F. Aymerich; J. W. Tong; Z. Y. Wang (Advances in Materials Science and Engineering, 2014)
The delamination buckling and growth behaviors of a cross-ply composite laminate with damage induced by low velocity impact are investigated optically using three-dimensional digital image correlation (3D-DIC) method. For the 3D deformation measurement, the 3D-DIC setup comprised of two CCD cameras was adopted. The rectangle specimen was impacted under the impact energy of 7.0 J using a drop-weight testing machine, and the impact damage was detected by means of X-ray nondestructive evaluation (NDE) technique. The 3D deformation field measured with the optical system clearly reveals that the delamination buckling characteristic of the specimen mainly appears local deformation mode under compression after impact test. Moreover, the behavior of delamination growth evaluated by the 3D-DIC optical method reasonably agrees with the NDE observed damage result after compression.